2013
DOI: 10.1080/01635581.2013.806936
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium Concentration and Prostate Cancer Risk: A Multicenter Study

Abstract: This study sought to further evaluate the possible effects of serum calcium level on prostate cancer (PC) risk, with considering the age, body mass index (BMI), and sex steroid hormones. Using data from a prospective multicenter study, serum calcium concentration, as well as thorough demographic and medical characteristics, were determined in 194 cases with newly diagnosed, clinicopathologically confirmed PC and 317 controls, without any malignant disease, admitted to the same network of hospitals. Serum total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Our findings that higher serum calcium concentrations increased the risk of incident PCa are consistent with laboratory studies that show that calcium promotes growth of PCa cells . There are few epidemiologic studies on serum calcium and incident PCa . The Malmo Diet and Cancer Study cohort showed a positive relationship between albumin‐adjusted calcium and PCa among men aged 55–65 with a BMI <25.0 kg/m 2 (relative risk, 2.07; CI, 1.08–3.97) .…”
Section: Discussionsupporting
confidence: 89%
“…Our findings that higher serum calcium concentrations increased the risk of incident PCa are consistent with laboratory studies that show that calcium promotes growth of PCa cells . There are few epidemiologic studies on serum calcium and incident PCa . The Malmo Diet and Cancer Study cohort showed a positive relationship between albumin‐adjusted calcium and PCa among men aged 55–65 with a BMI <25.0 kg/m 2 (relative risk, 2.07; CI, 1.08–3.97) .…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings with total and ionised serum calcium were reported when prostate cancer death was used as a surrogate outcome [ 160 ]. Nonetheless, an inverse association was observed in an Asian study [ 161 ]. No new studies have been published investigating the association between serum inorganic phosphate and risk of cancer.…”
Section: Bone Metabolismmentioning
confidence: 99%
“…In recent years, numerous studies have shown that there may be relationships between serum calcium levels and certain types of tumours, however, the results are inconsistent and inconclusive. [26][27][28][29][30][31][32] In addition, the relationship between serum calcium and uterine fibroids remains unclear and not well studied.…”
Section: Introductionmentioning
confidence: 99%